(untitled) (Research, Society and Development, 2023)
Brachycephalic syndrome presents with obstructive changes in the anterior respiratory tract that trigger clinical signs such as inspiratory dyspnea, snoring and syncope, reducing the quality of life of these animals. Diagnosis is based on physical examination, clinical signs present associated with imaging tests. The treatment of choice is surgical correction of obstructive anomalies. Obesity is a risk factor for brachycephalic syndrome, as it increases adipose tissue in the airways, narrowing the lumen and worsening respiratory effort. The body condition score is a subjective and semi-quantitative method that assesses body fat. Due to the reduction in quality of life and the potential risk of death, it is extremely important to study the impacts of obesity, age, reproductive status, sex and breed on the severity of clinical signs in these animals. Therefore, a retrospective study was carried out based on the medical records of dogs with brachycephalic syndrome treated in the city of Rio de Janeiro, in a veterinary service specialized in respiratory disorders in small animals. It has been demonstrated that there is an association between race, body condition score and advancing age with an increase in the degree of clinical manifestations. There was no association between the severity of clinical signs and sex and reproductive status. In view of this, it is extremely important to raise awareness among veterinarians and those responsible for maintaining an adequate body condition score and early indication of surgical treatment of obstructive anomalies to improve the quality of life of these animals.